A Novel In Vitro Tool to Study Cyst Nematode Chemotaxis - Laloum, Yohana; Ngala, Bruno; Ianszen, Mélina; Boulogne, Isabelle; Plasson, Carole; Fournet, Sylvain; Gotté, Maxime; Nguema-Ona, Éric; Le Roux, Anne-Claire; Gobert, Virginie; Driouich, Azeddine; Vicré, Maïté (Frontiers in Plant Science, 2020)
This study presents a novel three-dimensional (3D) tool “3D in vitro choice” for chemotaxis assays with nematodes. The original 3D in vitro choice was customized through digital printing. Freshly hatched second stage juveniles (J2s) of the potato cyst nematode Globodera pallida were used as the nematode model to illustrate chemo-orientation behaviour in the 3D system. The efficiency and reliability of the 3D in vitro choice were validated with 2% Phytagel as navigation medium, in three biological assays and using tomato root exudates as a positive attractant as compared with water. For each biological assay, J2s were hatched from the same population of a single generation glasshouse-cultured cysts. This novel easy to use and low-cost 3d-device could be a useful replacement to Petri dishes assays in nematode behavioural studies due to the ease of deposition of nematodes and test substances, coupled with its distinctive zones that allow for precision in choice making by the nematodes.